Design of vibration damping test mechanism for suspension system of high speed tracked vehicle based on vertical linkage decoupling. (December 2021) - Liu, Xuedong; Guo, Yong; Chen, Zhewu; Dai, Juchuan; Lin, Qihui; Quan, Song
The suspension test-rig is restricted by the compound swing motion of the load wheel in a high-speed tracked vehicle, and cannot test the damping performance for the suspension system of the high-speed tracked vehicle with the track. A vibration damping testing mechanism using vertical linkage to decouple the compound swing motion of the load wheel is proposed for suspension performance testing with the track. Using Hertz elastic contact theory to solve the stiffness coefficient between load wheel and excitation wheel, a virtual prototype model for vibration damping test mechanism with vertical linkage is established in ADAMS. Correctness of the virtual prototype model is verified by experiment. The motion decoupling ability of the vibration damping testing mechanism is verified by simulation. The dynamic characteristics for each pair of guide and slider in vibration damping testing mechanism are analyzed under the condition of maximum excitation force and displacement, and the selection criteria of slider and guide contained in the motion pair components are acquired. The mechanism decouples the compound swing motion of the load wheel successfully, and can make suspension system performance testing in high-precision for the high-speed tracked vehicle with track realized, playing an important role in parameters design and performance optimization for the high-speed tracked vehicle.